Idea to Ink: Lessons From Failure to Publish - Alday, Sandra Seno (Journal of management education, 2025)
Writing and publishing are critical components of an academic career. For many years however, my idealized notions of scholarly writing were demolished by painful and traumatic attempts to publish. The significant time and effort poured into crafting an academic article yielded desk rejection after desk rejection, at times unkind and unhelpful reviews, and a growing pile of unsent manuscripts gathering cyber dust in deliberately forgotten archived folders. I was both astounded and relieved at the discovery that I was not alone in my frustration. So, I turned my academic publishing failure into a subject of research. In this essay, I reflect on what it means to be a scholar and share the lessons I learned about the common blind spots that often lead to a failure to publish. Using management education scholarship as an example, I break down my writing process into stages, identify pitfalls at each stage, and describe the writing guardrails I put in place to keep my academic manuscript drafts on track. I share these lessons not from a place of exceptional success but from a place of failure, recognizing that lessons from many unsuccessful attempts offer equally important insights into what it means to succeed.